2000
DOI: 10.1001/archinte.160.14.2193
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Longitudinal Declines in Dehydroepiandrosterone Sulfate Concentrations and Cognitive Performance in Older Men

Abstract: Background:The observation that dehydroepiandrosterone (DHEA) concentrations decrease markedly with age has led to the hypothesis that declining DHEA concentrations may contribute to age-related changes in cognition. In the United States, DHEA is widely available as an over-the-counter supplement that individuals are using in an effort to ameliorate age-related cognitive and physical changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 29 publications
4
26
1
Order By: Relevance
“…We found a global trend to decline of DHEAS level over the 7 years at 2.3% per year among men and 3.9% per year among women. This decline is consistent with those found by several (20,21,23,24) but not all authors (19). Despite this global decline, we found an increase of DHEAS level in approximately one-third of our subjects (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found a global trend to decline of DHEAS level over the 7 years at 2.3% per year among men and 3.9% per year among women. This decline is consistent with those found by several (20,21,23,24) but not all authors (19). Despite this global decline, we found an increase of DHEAS level in approximately one-third of our subjects (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the evolution of the DHEAS level was inversely correlated with the baseline DHEAS level, leading to a decrease of DHEAS level when the initial DHEAS concentration was high and to an increase when the initial DHEAS level was low. This relationship was probably because of a regression toward the mean and has been found in other longitudinal studies (19,20). We found no significant relationship between the evolution of DHEAS level and several health parameters, even those known to be cross-sectionally associated with this level (18).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…These observations give rise to speculation that DHEA secretion in large amounts may be a unique adaptation contributing to the relative longevity of the human species, and that the agerelated decline in DHEA contributes to senescence. However, there has been difficulty in trying to correlate endogenous human DHEA levels with age-related changes in body composition or function (including immune function, insulin sensitivity and cognitive function), generally weak or non-significant relationships have been identified (Straub et al, 1998;Berr et al, 1996;Maccario et al, 1999;Abbasi et al, 1998;Abassi et al, 1998;Kostka et al, 2000;Haffner et al, 1994;Phillips, 1996;Kalmijn et al, 1998;Moffat et al, 2000). DHEA treatment of older men and women has not been convincingly demonstrated to have significant clinical benefits, with the exception of a study by Morales et al (1994) showing improvement in self-reported physical and psychological well-being in post-menopausal women.…”
Section: Dehydroepiandrosteronementioning
confidence: 99%